Often Overlooked Diagnosis: Median Arcuate Ligament Syndrome as a Mimicker of Crohn's Disease. Issue 10 (26th October 2021) - Becker, Erica; Mohammed, Turab; Wysocki, John
ABSTRACT: Median arcuate ligament syndrome occurs when the celiac artery and/or the celiac plexus nerves is compressed by the median arcuate ligament during expiration causing a variety of gastrointestinal symptoms. Here, we present a case of median arcuate ligament syndrome in a persistently symptomatic 35-year-old man that presented as a mimicker of Crohn's disease. Symptomatology, computed tomography angiography, and abdominal ultrasound Doppler were consistent with celiac artery compression syndrome. After surgical decompression of the ligament and removal of the celiac ganglion, he reported a definitive relief of abdominal pain and resolution of symptoms.